2008
DOI: 10.1128/iai.00021-08
|View full text |Cite
|
Sign up to set email alerts
|

EmaA, a Potential Virulence Determinant of Aggregatibacter actinomycetemcomitans in Infective Endocarditis

Abstract: The gram-negative fastidious human oropharyngeal Aggregatibacter actinomycetemcomitans is implicated in the etiology of infective endocarditis. EmaA, an oligomeric coiled-coil adhesin homologous to YadA of Yersinia enterocolitica, was hypothesized to mediate the interaction of A. actinomycetemcomitans with collagen. Collagen, the most abundant protein in human bodies and the main component of extracellular matrix (ECM), predominates in the supporting tissue of cardiac valves. To extend our earlier studies usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 40 publications
1
78
0
1
Order By: Relevance
“…Aggregatibacter actinomycetemcomitans strain VT1729, serotype b, expressing the green fluorescent protein (obtained from the University of Vermont, Burlington, VT, USA) was originally derived from A. actinomycetemcomitans clinical isolate SUNY 465 (35). This serotype b strain was used in this study because of its high pathogenicity and high prevalence in periodontal disease in the United States (15,16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregatibacter actinomycetemcomitans strain VT1729, serotype b, expressing the green fluorescent protein (obtained from the University of Vermont, Burlington, VT, USA) was originally derived from A. actinomycetemcomitans clinical isolate SUNY 465 (35). This serotype b strain was used in this study because of its high pathogenicity and high prevalence in periodontal disease in the United States (15,16).…”
Section: Methodsmentioning
confidence: 99%
“…This serotype b strain was used in this study because of its high pathogenicity and high prevalence in periodontal disease in the United States (15,16). Following previously described methods, A. actinomycetemcomitans was initially plated on 3% Trypticase soy broth and 0.6% yeast extract (TSBYE) 1.5% agar plates with 100 g/ml ampicillin (35). Aggregatibacter actinomycetemcomitans was then grown for 2 days in a 10% CO 2 incubator at 37°C and expanded in TSBYE broth containing 100 g/ml ampicillin overnight in 10% CO 2 at 37°C on a shaker.…”
Section: Methodsmentioning
confidence: 99%
“…The competition assay was performed as described previously (45). Briefly, 1 ml of midlogarithmic-phase cells from the wild type and the rmlC mutant, equivalent to 2.5 ϫ 10 8 CFU in sterile PBS, was used for each assay.…”
Section: Vol 192 2010 Glycosylation Of Emaa 1397mentioning
confidence: 99%
“…The carboxyl termini of the proteins assume ␤-barrel structures required for pore formation and translocation of the molecules through the outer membrane, similar to those of other type V c autotransporter proteins (14). Recently, we have demonstrated that EmaA is important in the initiation of infective endocarditis in a rabbit model of infectious endocarditis (45).…”
mentioning
confidence: 99%
“…The Aae and ApiA proteins promote attachment of A. actinomycetemcomitans to human buccal cells and GECs (Asakawa et al, 2003;Rose et al, 2003;Fine et al, 2005), while EmaA binds type I collagen, a mechanism also associated with the initiation of infective endocarditis (Tang et al, 2008) (Fig. 1).…”
Section: Auto-transporter Adhesins -Emaamentioning
confidence: 99%